Influence of folic acid on pregnancy outcome: Review study - Abdulmalek, Lubna (Libyan Journal of Science &Technology, 2022)
Adequate folic acid intake is essential throughout gestation to ensure normal fetal growth and development. Although the causal relationship between the deficiency of folic acid (Plasma total homocysteine"tHcy" level is elevated) and risk of neural tube defects are well proved, the relation between folic acid deficiency and other pregnancy complications is still un clear. The present study aims to review the data published about the relationship between serum folate and pregnancy complications. By reviewing 57 studies, this study concludes that folic acid deficiency leads to elevate plasma homocysteine, which increased risk of serious complications of pregnancy and delivery. So, it is recommended for women to take 400 microgram of folic acid supplements daily, before pregnancy to prevent those complications.